2019
DOI: 10.1007/s42452-019-0843-3
|View full text |Cite
|
Sign up to set email alerts
|

A review of heterogeneous calcium oxide based catalyst from waste for biodiesel synthesis

Abstract: Biodiesel is one of the most promising method to replace the fossil fuels because it is more environmentally friendly. Nevertheless, biodiesel manufacturing costs are much higher compared to conventional fossil fuels. Thus, the biodiesel should be synthesizing from reusable wastes to minimize the production cost. Homogeneous catalyst is the most common catalyst employed in the commercial biodiesel field. However, there are some drawbacks in using homogeneous catalyst in the reaction such as the difficulties fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…Investigations have revealed that chicken eggshells which hitherto have been considered as dumpsite waste can be recovered, reused, and regenerated to enhance their applications. Various researchers have experimented with the utilization of chicken eggshells as an environmentally friendly catalyst for transesterification reactions with good and encouraging outcomes [10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Investigations have revealed that chicken eggshells which hitherto have been considered as dumpsite waste can be recovered, reused, and regenerated to enhance their applications. Various researchers have experimented with the utilization of chicken eggshells as an environmentally friendly catalyst for transesterification reactions with good and encouraging outcomes [10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, transition metal oxides, zeolites, or activated carbon can also function as catalysts with acidic functionalities [69]. The use of solid catalysts derived from biomass such as diatomic earth, animal bones, seashells, or eggshell, has been proposed as more ecological alternatives [70]. This vast catalog of catalysts allows choosing the best system depending on the nature and quality of the oil, its availability, and the economic situation of the biorefinery or rural plant.…”
Section: Catalystsmentioning
confidence: 99%
“…Traditional biodiesel production methods utilize homogeneous conditions in the presence of bases or an acid catalyst such as sulfuric acid and sodium hydroxide 8 .These homogeneous systems suffer from limitations such as corrosion of reactors, difficult recovery and recyclability of catalyst and environmental pollution 9 , 10 . In this context, heterogeneous catalysts provide more advantages over homogeneous catalysts, such as recyclable 10 , 11 , ease separation-purification process 12 , high glycerol purity 13 , and not corrosive 14 . To date, numerous solid acid and base catalysts with tunable structural and surface functionalities have been offered, and many of them shows high catalytic activity for biodiesel production yield.…”
Section: Introductionmentioning
confidence: 99%